運用互動電子白板與小組合作學習策略輔助國小四年級摘寫國語課文大意之成效研究 A Study of the Interactive Electronic Whiteboard and Cooperative Learning for Fourth Grade in Language Arts of Summarizing Text - 黃郁婷 Huang, Yu-Ting (National Changhua University of Education, 2010)
許多研究顯示大意摘要能力是理解文章的基礎能力，更是讀書學習的必備能力，然而許多教師花費相當大的心力在大意摘要教學上，學生仍不得其要領。本研究的目的希冀運用互動電子白板所建構的數位化教學與學習的環境，並結合小組合作學習之優勢，以改進目前講授大意教學的模式，提升學生的參與感與專注力，進而增進學生之摘寫大意能力。而本研究採準實驗研究法之不等組前後測設計，以國小四年級四個班級的學生為研究對象，四個班級均接受不同教學方式，分別為互動電子白板與小組合作學習組、互動電子白板組、小組合作學習組以及對照組。研究分析以SPSS 軟體進行共變數分析，以驗證相關研究假設；此外，也透過教室觀察及文件記錄來蒐集資料，並訪談教師與學生，以便對研究成效加以補充、解釋與檢證。本研究結果發現： 1.不同教學方式與不同語文能力的學生在「摘寫課文大意能力」的表現上均有顯著差異。互動電子白板與小組合作學習組的學生優於小組合作學習組、互動電子白板組及一般教學組。而高能力學生優於中、低能力學生；中能力學生表現亦優於低能力學生。 2.教師與學生均認為互動電子白板與小組合作學習策略輔助摘寫課文大意可以幫助學生集中注意力、有效提升參與度和增進教學和學習效率。 最後，綜合以上研究結果，提出建議供教師實務教學以及未來研究者參考。 Reports both abroad and within the country showed that students found it difficult to summarize articles. The use of educational technology in improving the ability of student's to create summaries was thus a critical issue. A high tech product, such as an Interactive WhiteBoard, had the potential to revolutionize the application of digital instruction and became an indispensible teaching tool. The researcher attempts to create a platform of learning by utilizing the Interactive WhiteBoard and combining it with a team cooperative learning strategy. It was the objective of this researcher to transform the traditional method of lecturing into a more modern and effective approach through the use of digital technology. The main objective was to motivate the students and got them more involved with the reading material and the creation of summaries. The methodology of this study was mainly based upon the nonequivalent pretest-posttest of the quasi-experimental design. The subjects of this study were four classes of fourth grade students. The conclusions of the experiment were as follows: 1.Group one （Interactive WhiteBoard and cooperative learning） advanced learning students and scored the highest out of all the groups in "summary evaluation scale" . 2.Teachers and students believed that Interactive WhiteBoard and cooperative learning strategy greatly improved the student's concentration, efficiency, and effectiveness. Finally, the researcher explained how Interactive WhiteBoard and cooperative learning strategy could be integrated into language arts instruction lessons at the elementary school level. These ideas could be referenced by both instructors and researchers.